2018
DOI: 10.1177/1741143218817562
|View full text |Cite
|
Sign up to set email alerts
|

Principals and stress: Few coping strategies for abundant stressors

Abstract: Various job demands continue to be very stressing and exhausting for school administrators who have to work under unprecedented pressure. This qualitative study explores the various stressors school administrators experience and the coping strategies they utilize to manage their stress. Findings show that the various stressors experienced by the school administrators do affect their job performance and their own wellbeing. Principals mentioned three main types of stressors related to work, relationships and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(159 citation statements)
references
References 51 publications
7
144
0
8
Order By: Relevance
“…Previous research revealed that most of the high levels of academic stress in junior and senior high school students during learning were caused by learning with an online system (Macintyre et al, 2020). The academic stressors that are most often revealed are student preparation for exams (Mahfouz, 2018), competence in getting good grades, and mastery of material that must be caught quickly at every meeting (Dolfen, King, Schwabe, Swinnen, & Albouy, 2019) and learning media factors which is considered unsuitable for them, (Yikealo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed that most of the high levels of academic stress in junior and senior high school students during learning were caused by learning with an online system (Macintyre et al, 2020). The academic stressors that are most often revealed are student preparation for exams (Mahfouz, 2018), competence in getting good grades, and mastery of material that must be caught quickly at every meeting (Dolfen, King, Schwabe, Swinnen, & Albouy, 2019) and learning media factors which is considered unsuitable for them, (Yikealo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of awareness of one’s own way of acting can lead to behaviors that are not functional to the work context, to the quality of the interaction with one’s colleagues and to the nature of the task required at the time [ 50 ]. By investing in one’s mindfulness, one can expect to break the old automatisms in favor of new behaviors, effective even in difficult times, as indicated by Weick and Sutcliffe, who believe it is necessary to rely on a mindfulness-oriented approach when there is a need to make a quick and important decision, giving priority to one’s competence (or that of one’s co-workers), rather than relying on one’s authority.…”
Section: Discussionmentioning
confidence: 99%
“…The study recommends a stress management clinic specifically for younger school heads to support them build resilience against the stressful nature of the job. Also, considerations could be made for physical exercises, spending time with kids and family and participating in hobby activities (Mahfouz, 2020). Though job satisfaction seems to be high among school heads, the fact that older school heads were less satisfied but long-serving school heads were more satisfied was revealing.…”
Section: Recommendationmentioning
confidence: 99%